(untitled) (KYAMC Journal, 2024)
Background: Poisoning is a significant global public health problem. In many countries acute poisoning is one of the common scenarios in the emergency department of any general hospitals globally but it’s pattern may vary in different parts of the world and even may be different regional variation in the same country. Objective: In this study our main goal is to evaluate the Profile of Poisoning cases attending in the Emergency Department of Khwaja Yunus Ali Medical College & Hospital (KYAMCH), Enayetpur, Sirajganj. Materials and Methods: This cross-sectional study was carried out at the emergency department of Khwaja Yunus Ali Medical college and hospital (KYAMCH), Enayetpur, Sirajganj from January’21 to December’21. Total 80 poisoning cases were collected by using a pre-designed format from Emergency register book/ records, for the study, were those who had undergone exposure to poison either by household or agricultural pesticides, stings bite or snake bite, industrial toxins or toxic plants, drug or miscellaneous products. Results: During this study, the majority were belonging to 16-30 years age group (65%), (55%) were Female and (75%) were Muslims, most of the cases were Suicidal (70%) and no Homicidal case was recorded. Besides that, (20%) poisoning cases were due to Barbiturate, followed by (12.5%) were Organo-phosphorous compound poisoning as well as copper sulphate poisoning. (35%) victim came to hospital within 2 hours to 6 hours and (73.75%) cases were shifted to General bed, followed by (11.25%) cases were Admitted in ICU and (31.25%) cases were found during spring. Conclusion: From our study, we can say that suicidal cases and Barbiturate poisoning were commonly seen. Besides that, young and middle-aged female people are mostly vulnerable to poisonous cases. KYAMC Journal Volume: 14, No: 03, October 2023: 116-119.